IMPROVING MECHANISMS FOR THE DEVELOPMENT OF SPEECH CULTURE IN NON-PHILOLOGISTS STUDENTS AS AN INITIAL PEDAGOGICAL PROBLEM (American Journal of Interdisciplinary Research and Development, 2024)
The article is devoted to current issues of teaching the Russian language, improving the oral speech of students of non-philological higher education institutions. The article explores and reveals the methodology of scientific study of the problem, the effective development of speech competence in mastering someone's speech, as well as the working principles and aspects of culture formation in society and the professional environment. The topic of research in this article is devoted to the problem of problems that require a modern scientific approach and reconsideration from a scientific and methodological point of view.